Rare but lethal disease of childhood: metastatic, muscle invasive bladder cancer - Serdar Aykan; Emrah Yuruk; Murat Tuken; Mustafa Zafer Temiz; Sule Ozsoy (MDPI AG, 2015)
Bladder cancer is the most common malignancy of urinary tract and the seventh most common cancer in men with the peak incidence in the sixth decade of life. Our knowledge about bladder tumors in pediatric age group mainly relies on case series. The reported cases are mostly low grade and non-muscle invasive. We herein present a case of a 17- year-old male with metastatic high-grade muscle-invasive bladder cancer who was presented with macroscopic hematuria and flank pain.